Design of a Torsion Measurement System of High Stiffness and Sensitivity to Study Yield in Low Carbon Steels. - Tuling, Alison S (My University, 2007)
Strain ageing anisotropy, a surprising property of iron, implies that interstitials, which are non-lattice obstacles, can give non-symmetrical opposition to glide. Al- though this has been investigated by others, it is shown that it is di±cult to eliminate extraneous residual stresses during testing. An Avery torsion machine was adapted for the study of strain ageing anisotropy through the design of a torque and twist measurement system. This required the optimization of sensitivity, stiffness and me- chanical stability criteria, while ensuring practicality. When a ¯ne-grained sample with circumferential groove was tested a sharp yield point and lack of yield after ageing in the reverse direction was observed. Although more testing is required, it con¯rms the results of other researchers. In testing it was found that the quality of the sample machining was critical in achieving an accurate yield, and the groove design must be reviewed and improved. While the system measured to the required torque resolution, the strain measurement system could be improved by redesign and better calibration statistics.
Student Number : 9102778K - MSc(Eng) dissertation - School of Chemical and Metallurgical Engineering - Faculty of Engineering and the Built Environment
Keywords: Bauschinger effect; torsion; steel; strain ageing